Suicide attempts in French prisons: results of the TARTARE survey. (1st March 2011) - Encrenaz, G; Miras, A; Contrand, B; Pujos, S; Galera, C; Michel, G; Lagarde, E
Abstract : Objectives: To describe suicidal behaviours in prisons and to determine factors associated with suicide attempts during imprisonment. Methods: All inmates of a prison for prisoners awaiting trial (Bordeaux, France) were eligible for this cross-sectional study. 375 inmates have been face-to-face interviewed by an experienced psychologist. Sociodemographic data, imprisonment conditions, health status and healthcare utilisation, mental health, impulsivity, aggressiveness, interpersonal violence (victim and perpetrator status) and suicidal behaviours were documented. Results: The incidence of suicidal attempts during imprisonment was equal to 12.9 per 100 persons-year. Having made a suicide attempt during imprisonment was associated with being victim of violence without perpetrating it (adjusted OR=7.5), having children (adjusted OR=3.5), suffering from depressive and anxious symptoms (adjusted OR=3.4) and complaining about the prison noise (adjusted OR=3.7). Other factors, in particular a personal history of suicide attempts, were not associated with the risk of suicide attempts during imprisonment. Discussion: The major risk factor of suicide attempts was being victim of violence. These results could help to improve screening checklists of inmate suicide risk already used in prisons. However, all data were self-reported but have been improved using data recorded by the prison administration when they were available.